2009
DOI: 10.1080/13557850802227031
|View full text |Cite
|
Sign up to set email alerts
|

Patient–provider race-concordance: does it matter in improving minority patients’ health outcomes?

Abstract: Objective To understand if patient–provider race-concordance is associated with improved health outcomes for minorities. Design A comprehensive review of published research literature (1980–2008) using MEDLINE, HealthSTAR, and CINAHL databases were conducted. Studies were included if they had at least one research question examining the effect of patient–provider race-concordance on minority patients’ health outcomes and pertained to minorities in the USA. The database search and data analysis were each inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 35 publications
6
145
3
Order By: Relevance
“…[46][47][48] However, there are other means by which physicians can demonstrate respect or trust without requiring race or ethnic concordance, including increasing familiarity with patients and understanding their cultural values and beliefs. 49,50 Finally, CAM presented itself as a topic that physicians leveraged to demonstrate cultural sensitivity. Physicians' and patients' attitudes about CAM reflected cultural differences that affected care.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48] However, there are other means by which physicians can demonstrate respect or trust without requiring race or ethnic concordance, including increasing familiarity with patients and understanding their cultural values and beliefs. 49,50 Finally, CAM presented itself as a topic that physicians leveraged to demonstrate cultural sensitivity. Physicians' and patients' attitudes about CAM reflected cultural differences that affected care.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies of patient-provider racial concordance report mixed results. 12 The health literacy measures used in this study have limitations. The TOFHLA measures reading comprehension and numeracy, while the REALM assesses word recognition and pronunciation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two suggested sources of disparities in patient outcomes have been the provider attitudes that impact communication and interaction with the patient 11 and racial concordance between providers and patients. 12 Patients can address racial concordance in their choice of a provider, whereas the providers can address communication and interaction issues.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have found same-race/ethnicity dyads to have more effective communication, others reported no statistically significant differences between same-and mixed-ethnicity dyads. Meghani et al (2009) reviewed patient-provider, race concordance and reported that of the 27 studies approximately one-third were Caucasian, one-third were African American, and 13% were Hispanic. The authors found patient provider race-concordance was associated with positive health outcomes for minorities in nine studies, while eight studies found no association of race-concordance with the outcomes studied and 10 presented mixed findings.…”
Section: Recommendationsmentioning
confidence: 99%